Polarised television audiences. The outcomes of the Estonian and European audiovisual media policies - Jõesaar, Andres (Žurnalistikos tyrimai, 2015)
The European Union’s (EU) liberalisation of media policies and its content quality bias towards economic efficiency has resulted in a situation where, in some small markets like Estonia, the audience is divided into two parts. The Russian-speaking audience in Estonia mainly follows Russian state TV channels, and the Estonian-speaking audience watches Estonian television channels. This has happened even though the EU media policy should ensure freedom of information, diversity of opinion and media pluralism. Findings from the Estonian case study show that despite the noble aim of the EU media policy, Estonia has two radically different information fields: Estonian-language media promotes European values, and Russian state media, enjoying high popularity among the Russian speakers, promotes ‘Putin’s values’. The question is whether the EU legal instrument — Audiovisual Media Service Directive (AVMSD) — is an efficient tool when disinformation from third countries is disseminated with the aim of gaining a political influence over the EU member states’ citizens. The recommendation is that the AVMSD should be revised in a way that prevents unfair competition directed from third countries and tools should be developed to compensate for market failures.